Tumor suppressor miR‐139‐5p targets Tspan3 and regulates the progression of acute myeloid leukemia through the PI3K/Akt pathway. Issue 3 (26th October 2018) - Zhang, Ronghui; Tang, Ping; Wang, Fang; Xing, Ying; Jiang, Zhongxing; Chen, Shaoqian; Meng, Xiaoli; Liu, Linxiang; Cao, Weijie; Zhao, Huayan; Ma, Ping; Chen, Yanli; et al.
Abstract: Dysregulation of microRNAs is closely implicated in the initiation and progression of human cancers including acute myeloid leukemia (AML). Though miR‐139‐5p was reported to be a potent tumor suppressor in adult AML, its underlying molecular mechanism in AML remains to be further defined. Herein, quantitative real‐time polymerase chain reaction (qRT‐PCR) and Western blot analysis were conducted to determine the expressions of miR‐139‐5p and tetraspanin3 (Tspan3) in AML patients and cells. Luciferase reporter assay, qRT‐PCR, and Western blot analysis were carried out to detect the interaction between miR‐139‐5p and Tspan3. Cell proliferation, cell cycle distribution, invasion, and migration were evaluated by cell counting kit‐8, flow cytometry, transwell invasion, and migration assays, respectively. Western blot analysis was conducted to determine phosphorylated‐protein kinase B (Akt) and Akt levels. We found that a significant reduction in miR‐139‐5p expression and a prominent increase in Tspan3 expression were observed in AML patients and cells. Tspan3 was confirmed as a direct target of miR‐139‐5p and was negatively modulated by miR‐139‐5p. Rescue experiments showed that overexpression of miR‐139‐5p constrained cell proliferation, invasion and migration capabilities, and induced cell cycle arrest at the S phase in AML cells, which were partially reversed by Tspan3 overexpression. In addition, we found that miR‐139‐5p suppressed the phosphoinositide 3‐kinase (PI3K)/Akt pathway in AML cells by targeting Tspan3. In conclusion, our study concluded that miR‐139‐5p suppressed the leukemogenesis in AML cells by targeting Tspan3 through inactivation of the PI3K/Akt pathway, providing a better understanding of AML progression. Abstract : miR‐139‐5p expression was significantly decreased, and tetraspanin3 (Tspan3) expression at both mRNA and protein levels was markedly increased in acute myeloid leukemia (AML) patients and cells. Tspan3 was identified as a target of miR‐139‐5p and was negatively regulated by miR‐139‐5p. miR‐139‐5p suppressed the leukemogenesis in AML cells by targeting Tspan3 through inactivation of the PI3K/Akt pathway, providing a better understanding of AML progression.